The Effect of Intense Exercise on Equine Serum Proteoglycan-4/Lubricin - Matheson, Austyn; Regmi, Suresh C.; Jay, Gregory D.; Schmidt, Tannin A.; Scott, W. Michael (Frontiers in Veterinary Science, 2020)
Objective: Local biological and biomechanical-stimuli modulate proteoglycan-4 secretion within synovial joints. For the horse, changes to proteoglycan-4 concentration and function are notable in acute joint injury and osteoarthritis. Proteoglycan-4 is also present in the blood, however the effect of exercise on equine serum levels is unknown. The overall objective of this study was, therefore, to investigate the effect of intense exercise on serum proteoglycan-4 in racehorses. Methods: Samples of blood were taken from racehorses (n=12) during a chuckwagon racing event (Alberta, Canada). The chuckwagon race is a sprint racing event where teams of horses pull a combined 1325 lbs of wagon and driver around a 5/8th mile of dirt track, racing at full gallop to the finish. Blood samples were collected 30-minutes before the race start, and several timepoints post-race: 5-minutes, 90-minutes, 3-hours, 12-hours, and 23-hours. Proteoglycan-4 concentrations in serum were quantified by enzyme-linked-immunosorbent-assay using recombinant-human proteoglycan-4 standards and anti-proteoglycan-4 mAb 9G3. The molecular weight of immunoreactive proteoglycan-4 in serum was assessed by western blot. Results: Proteoglyan-4 in serum demonstrated the expected high MW immunoreactivity to mAb 9G3, consistent with that of full length PRG4. Serum proteoglycan-4 decreased five-minutes post-race from baseline concentration (0.815 ± 0.175 to 0.466 ± 0.090 µg/mL, µ ± SEM, p<0.01). In addition, decreased serum proteoglycan-4 from baseline approached significance at 3-hours (0.570 ± 0.128 µg/mL, p=0.055) and 23-hours (0.520 ± 0.087 µg/mL, p=0.071) post-race. Conclusions: The concentration of serum proteoglycan-4 in racehorses decreased significantly five minutes post-exercise. A potential explanation for this finding could be increased proteoglycan-4 clearance from the circulation. Further investigations could extend to complete the detailed characterization of proteoglycan-4 structure and its potential function within the blood as it relates to joint health and exercise.